God, Israel, and the Gentiles. Rhetoric and Situation in Romans 9–11 - Campbell, William S. ca. 20./21. Jh. (Journal of Semitic studies, 2002)
God, Israel, and the Gentiles. Rhetoric and Situation in Romans 9–11 Johann D.Kim (SBL Dissertation Series 176). Society of Biblical LiteratureAtlanta 2000xvii + 178$45.00 0‐88414‐014‐8 , 1University of Wales, Lampeter